Maintaining the physical quality of jasmine flowers (Jasminum sambac) during its storage using low temperature treatments - Nurila, I.; Jumeri, Jumeri; Falah, Muhammad Affan Fajar (International Society for Horticultural Science, 2022)
The flower of jasmine (Jasminum sambac) is an important horticultural product for the export industry in Indonesia. However, current practices during postharvest handling and storage are not successful in preserving/protecting the physical appearance of the flowers, which is a key aspect in determining their commercial value. There is a need to reassess storage conditions for jasmine flowers in order to address carefully the postharvest issues. The objective of the study was to determine the effects of various environmental conditions (temperature and relative humidity) on the physical characteristics of jasmine flowers. Using flower samples that were obtained from Pemalang city, Central Java, the effects of varying temperatures and relative humidity were measured by using parameters such as weight loss, discoloration and whiteness index, and freshness index. Our results show that low temperature storage condition (4±1°C and RH 82-91) usually preserves the physical quality of jasmine flowers by delaying their deterioration as compared to medium (18±2°C and RH 87-93) and high (28±2°C and RH 64-89) temperature conditions.